2000
DOI: 10.1098/rspb.2000.1172
|View full text |Cite
|
Sign up to set email alerts
|

Developmental trade–offs and life histories: strategic allocation of resources in caddis flies

Abstract: Resource allocation trade-offs during development are potentially very important in the evolution of organism morphology and life-history strategy However, they have rarely been demonstrated empirically. To what extent the division of limited resources between growing organs is a consequence of particular developmental pathways or varies strategically in line with life-history predictions is unknown. It has been demonstrated in a number of holometabolous insects that altering the resources available at pupatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
78
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(82 citation statements)
references
References 22 publications
3
78
1
Order By: Relevance
“…Larvae fed on DRY leaves also had a higher %P, which, consistent with the growth rate hypothesis, could be related to P-rich rRNA (Elser et al 2003), and thus, contributed to high growth rates in this treatment. The decrease in %N in DRY detritivores' body tissue, probably in response to its lower concentration in leaves, might also have contributed to the relative increase in P. Although changes in N were modest, their effects on case-building detritivores could be noteworthy (Stevens et al 2000;Mckie 2004), as the allocation of protein (silk) to case building appears to be a fixed trait (Friberg and Jacobsen 1999), and can reduce larval protein by up to 35% (Mondy et al 2011). Therefore, despite the lack of short time effects on growth (but see Frainer et al 2016), further effects on detritivore fitness cannot be excluded.…”
Section: Discussionmentioning
confidence: 99%
“…Larvae fed on DRY leaves also had a higher %P, which, consistent with the growth rate hypothesis, could be related to P-rich rRNA (Elser et al 2003), and thus, contributed to high growth rates in this treatment. The decrease in %N in DRY detritivores' body tissue, probably in response to its lower concentration in leaves, might also have contributed to the relative increase in P. Although changes in N were modest, their effects on case-building detritivores could be noteworthy (Stevens et al 2000;Mckie 2004), as the allocation of protein (silk) to case building appears to be a fixed trait (Friberg and Jacobsen 1999), and can reduce larval protein by up to 35% (Mondy et al 2011). Therefore, despite the lack of short time effects on growth (but see Frainer et al 2016), further effects on detritivore fitness cannot be excluded.…”
Section: Discussionmentioning
confidence: 99%
“…This result does not agree with the results of previous studies in other caddisfly species. Indeed, larvae of Odontocerum albicorne and Glyphotaelius pellucidus forced to rebuild a new case show a differential reduction of their thorax and abdomen sizes (Stevens et al, 2000). Nevertheless, because the formation of testes in L. rhombicus larvae occurs at the end of the final larval stage and because gametogenesis is complete at adult emergence (Le Lannic, 1975), the reduction in the abdominal mass of the males produced from the larvae forced to rebuild a case, relative to the control males (loss of 28% in dry mass), could indicate a decrease in their reproductive capacity.…”
Section: Discussionmentioning
confidence: 99%
“…Because most caddisfly adults feed minimally or not at all (Mosely, 1939), the acquisition of resources during the larval stage is crucial for growth, case construction, reproduction and maintenance. Several studies have shown that larvae forced to rebuild a case experience a severe increase in energy expenditure, and such an increase can impact the dispersal and reproductive capacities of the adults [Caddisfly (Stevens et al, 1999;Stevens et al, 2000;Jannot et al, 2007), Chironomid (McKie, 2004)]. In a previous study, we found that larvae of Limnephilus rhombicus Linnaeus (Trichoptera: Limnephilidae) forced to rebuild a case increased their oxygen consumption by 50% during the period of reconstruction, compared with control larvae (Mondy et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some other elements related to insect cold hardiness (for additional details see Table 2 in Danks 1996). Stevens et al 1999Stevens et al , 2000. However, the durability and effectiveness of cocoons for multiple purposes, such as water permeability and resistance to mechanical damage, predators, and ice inoculation, has not been measured (Danks 2004b).…”
Section: Cold Hardiness and Timementioning
confidence: 99%